AN INNOVATIVE WAY OF DEVELOPMENT OF HIGHER EDUCATION – A PREREQUISITE TO ENHANCE ITS QUALITY - O. Garashchuk; V. Kutsenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Improving the quality of education needs to move her to an innovative way of development. The paper states that innovation in education – a key condition of its availability, efficient use of resources. Innovations in Education author examines how the introduction of something new in higher education, the implementation of new ideas, new methods. Reviewed state of scientific and technical progress in Ukraine, noting that the volume of scientific and technical work performed by enterprises grows. Emphasizes the role of higher education, which is an integral component of the economy. Systematized indicators characterizing the level of development of higher education in Ukraine. The changes that have occurred and the factors that led to them. Emphasized the importance of implementing the various components of the innovation in the educational process and proved a number of measures for its development. Revealed the importance of financial components to provide the resource base for the transition of the educational sector in the innovation way of development. The need for structural changes in higher education, in training, which has a positive impact on the socio-economic performance of the country and the economic activity of the population. It is emphasized that confirm the activity of higher education transition to an innovative way of development is closely associated with this process in a secondary school. And therefore stresses the need for further computerization and informatization of secondary school and in higher education needs to accelerate the development and implementation of new learning technologies, formation of creative innovation teams and ensure their mobility, financial security model of higher education, including through public-private partnership.